Cyanobacteria-Based Bio-Oxygen Pump Promoting Hypoxia-Resistant Photodynamic Therapy - Sun, Tao; Zhang, Yingying; Zhang, Chaonan; Wang, Hanjie; Pan, Huizhuo; Liu, Jing; Li, Zhixiang; Chen, Lei; Chang, Jin; Zhang, Weiwen (Frontiers in Bioengineering and Biotechnology, 2020)
Hypoxia not only alters tumor microenvironment but leads to the tumor progression and metastasis as well as drug resistance. As a promising strategy, photodynamic therapy (PDT) can inhibit tumor by catalyzing O2 to cytotoxic reactive oxygen species. However, its effects were limited by hypoxia and in turn deteriorate hypoxia due to O2 consumption. Hereon, aiming to alleviate hypoxia and promote PDT, a bio-oxygen pump was created based on cyanobacteria, which are the only prokaryotic organisms performing oxygenic photosynthesis. Detailly, controlled-release PDT via loading indocyanine green into mesoporous silica nanoparticles was established. Then bio-oxygen pump based on a fast-growing cyanobacterium Synechococcus elongatus UTEX 2973 was tested and further packaged together with PDT to create an injectable hydrogel. The packaged hydrogel showed stable oxygen production and synergetic therapy effect especially towards hypoxia 4T1 cells in vitro. More importantly, strong in vivo therapeutic effect reaching almost 100% inhibition on tumor tissues was realized using PDT equipped with oxygen pump, with only negligible in vivo side effect on healthy mice from S. elongatus UTEX 2973. The new photo-oxygen-dynamic therapy presented here provided a promising strategy against hypoxia-resistant tumor and may worth further modifications for therapeutic application.